PENGARUH INSENTIF DAN PENEMPATAN PEGAWAI TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA TERHADAP KINERJA PEGAWAI DINAS PENDAPATAN DAERAH PROVINSI JAMBI - Yunan Surono; Rodesa Rodesa (Universitas Batanghari, 2016)
Human resource is an invaluable asset. Therefore, it is anticipated that HR is able to compete fairly for the employee displacement of the employer and job satisfaction perceived by employees.The purpose of this study was to examine the influence of remuneration, employee displacement and job satisfaction to employee performance. The influence of remuneration, employee displacement and job satisfaction tested both directly and indirectly through the performance.To test the above issues, the survey done in writing which were distributed to all employees in the Dinas Pendapatan Daerah Jambi Province. Framework of theory and data analysis is done using Path analysis. The results of this research indicate that the style of remuneration, motivation and job satisfaction influential support directly and indirectly to the performance of the employees.Analytical tool in this study using descriptive methods and verification. Where descriptive study using a range of scales, while the verification using path analysis or path analysis.These findings reflect that style of remuneration, employee displacement and job satisfaction is a key issue. The research results reveal that the results related to the performance of civil servants is essential to manage the Office of the Dinas Pendapatan Daerah Jambi Province. Remuneration and job satisfaction perceived by the employee will lead to better performance than what was expected. Keywords: Remuneration, Employee Displacement, Job Satisfaction and Employee Performance